Disentangling species-specific krill responses to local oceanography and predator’s biomass: The case of the Humboldt krill and the Peruvian anchovy - Díaz-Astudillo, Macarena; Riquelme-Bugueño, Ramiro; Bernard, Kim S.; Saldías, Gonzalo S.; Rivera, Reinaldo; Letelier, Jaime (Frontiers in Marine Science, 2022)
Euphausiids (hereafter “krill”) are one of the main components of the pelagic communities of the Humboldt Current (HCS). Their community dynamics have been well studied in central-southern Chile where upwelling is strongly seasonal, but little is known about the permanent-upwelling area of the HCS, which yields the largest fishery in the world, the Peruvian anchovy. We applied hierarchical generalized additive models with environmental and biological predictors to determine the main drivers of krill abundance, adjusting species-specific functions. We used a time series of 16 bi-annual surveys to study annual, seasonal, and spatial scales of variability of the four numerically dominant taxa: Euphausia mucronata (Humboldt krill), E. eximia, Stylocheiron affine, and Nematoscelis spp. The spatial pattern of the Humboldt krill (the dominant species) proved it is an upwelling-associated species, with higher abundances within 10 km from the coast. The other 3 taxa showed opposite spatial patterns with higher abundances offshore. The main covariates explaining krill abundances were the depth of the upper limit of the oxygen minimum zone (dOMZ) and the mean temperature of the water column. Humboldt krill was negatively correlated to both drivers, and the opposite effect was observed for the other taxa. Although many krill species are metabolically adapted to cope with the severe hypoxic conditions of this system, the Humboldt krill was the only species with higher modeled abundances when dOMZ was shallower. Chlorophyll-a remained high during all sampling periods, and it was an insignificant predictor for all taxa, suggesting food is not a limitation for krill in this highly productive system. The acoustic biomass of the Peruvian anchovy had a negative non-linear effect on the abundances of the Humboldt krill, and higher Humboldt krill abundances were found in areas with no anchovy hotspots. Our results indicate that krill in this system are susceptible to changes in temperature, oxygen, and upwelling conditions. Extreme events (e.g. heatwaves and ENSO events) are expected to increase in frequency and intensity, while climate change scenarios show a potential intensification of upwelling. These conditions could lead to distribution displacements and alter trophic interactions by modifying the distribution and biomass of the predator.